2008
DOI: 10.3399/bjgp08x277014
|View full text |Cite
|
Sign up to set email alerts
|

Signs and symptoms in diagnosing acute myocardial infarction and acute coronary syndrome: a diagnostic meta-analysis

Abstract: Diagnostic meta-analysis. MethodUsing MEDLINE, CINAHL, EMBASE, tracing references, and by contacting experts, studies were sought out that described one of the 10 signs and symptoms on one or both conditions. Studies were excluded if they were not based on original data. Validity was assessed using QUADAS and all data were pooled using a random effects model. ResultsSixteen of the 28 included studies were about patients who were non-selected. In this group, absence of chest-wall tenderness on palpation had a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 49 publications
4
81
0
2
Order By: Relevance
“…Previous reviews could not define an important role for signs and symptoms in general in the diagnosis of coronary artery disease and acute coronary syndromes. [8][9][10] Among the individual variables that were evaluated, age and history of prior myocardial infarction were effective for diagnosing typical angina (coronary artery disease), 9 and the absence of chestwall tenderness on palpation was effective for diagnosing acute coronary syndromes. 8,10 The variable "patient assumes pain is of cardiac origin" was not used in other studies and therefore remains a unique variable in our study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews could not define an important role for signs and symptoms in general in the diagnosis of coronary artery disease and acute coronary syndromes. [8][9][10] Among the individual variables that were evaluated, age and history of prior myocardial infarction were effective for diagnosing typical angina (coronary artery disease), 9 and the absence of chestwall tenderness on palpation was effective for diagnosing acute coronary syndromes. 8,10 The variable "patient assumes pain is of cardiac origin" was not used in other studies and therefore remains a unique variable in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Predictive scores have also been developed for use in emergency departments, mainly for the diagnosis of acute coronary syndromes. [11][12][13] To what degree these apply in primary care is unknown.…”
mentioning
confidence: 99%
“…In observational studies drug use in general has been reported to increase in the period before acute hospitalization due to a cardiac event suggesting no causal relationship between drug use and the adverse event but rather an effect of unmeasured confounding [8,9]. On the other hand, because of their potential similarity, prodromal symptoms of acute myocardial infarction (AMI) are sometimes interpreted as dyspepsia [10][11][12]; a mistake that represents a common cause of malpractice allegations in primary healthcare [13][14][15]. Further, patients with antecedents of acute coronary syndrome and atherosclerosis habitually take antiplatelet agents like aspirin or clopidogrel to prevent thrombotic complications and, in turn, are co-prescribed PPI to prevent dyspepsia which is a common side effect of antiplatelet therapy [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As the first doctors to see the patients, they are in very good position to make a proper diagnosis and apply the recommended therapy, which could save patients' lives, especially in rural areas where the nearest hospital is far away. The initial goal is to determine whether the patient needs to be referred for further testing to rule out an АMI (23). Differentiating ischemic from non-ischemic causes is often difficult, and patients with chest pain of ischemic etiology often appear to be well.…”
Section: Discussionmentioning
confidence: 99%